Effect of nitrogen rates on the growth and grain yield of a leaf early‐senescent rice mutant. (28th February 2021) - Xu, Yunji; Li, Ke; Zhu, Kuanyu; Tian, Yinfang; Yu, Qing; Zhang, Weiyang; Wang, Zhiqin
Abstract: Nitrogen plays a vital role in regulating leaf senescence and yield formation in rice ( Oryza sativa L.). However, little information is known about the effects of N rates on the growth and grain yield of rice plants with leaf early senescence. This study used a leaf early‐senescent rice mutant ( osled ) and its wild type (WT) (93‐11) and investigated how N rates of 0 kg ha –1 (0N), 240 kg ha –1 (240N), and 360 kg ha –1 (360N) influenced the main agronomic and physiological performance of the mutant osled . The results showed that 240N and 360N treatments increased grain yield of the osled plants by 201.5–222.9% and 266.4–287.9% as compared with 0N treatment, respectively, with the 360N treatment maintaining a similar agronomic nitrogen use efficiency (ANUE) as 240N. Leaf activity of the osled plants was enhanced with N supply levels showing increased leaf area, chlorophyll content, N content, and activities of N‐related enzymes and photosynthetic rate, and lowered malondialdehyde content. In contrast to 0N, the two N treatments significantly increased plant height, aboveground biomass, tiller number and percentage of productive tillers of both rice genotypes. Compared with 240N, the 360N treatment particularly increased grain weight and percentage of filled grains for the osled plants through improving leaf activity, root activity, and grain activity. These results verify that N treatment regulates leaf senescence and reduces yield loss of the osled plants, and simultaneously implied that the osled plants more positively respond to high N supply. Core Ideas: We mainly highlighted some agronomic and physiological performances of the rice mutant osled response to different N supply levels. Grain yield of the osled plants increased with N supply, accompanied by 360N treatment maintaining a similar agronomic N use efficiency as 240N treatment. The 360N treatment particularly increased grain weight and percentage of filled grains for the osled plants.